Perioperative nursing of a child with hemophilia B and adenoid hypertrophy undergoing surgery (1例血友病B患儿腺样体肥大的围手术期护理) - LYU Manjun (吕曼君); GUAN Xiaoli (官小莉) (中西医结合护理)
This paper summarized the perioperative nursing experience of a child with hemophilia B and adenoid hypertrophy undergoing surgery. The treatment and nursing plan was formed based on the multidisciplinary consultation and discussion. Health education about usage and precautions of prothrombin complex concentrate in replacement therapy was carried out before treatment. Based on the theory of enhance recovery after surgery, a comprehensive perioperative nursing interventions were carried out, including diet care, pain management, body temperature management, preoperative adaptive training. An effort was also made to enhance the psychological care, pre-discharge readiness assessment, discharge planning and guidance and continuous care after discharge. (本文总结1例血友病B患儿腺样体肥大围手术期的护理经验。经多学科会诊讨论并制定治疗护理方案, 告知替代治疗中凝血酶原复合物的使用方法及注意事项, 实施基于加速康复外科理念的围术期护理(饮食护理、疼痛管理、体温管理、术前适应性锻炼), 加强心理干预、出院前的出院准备度评估、出院计划与指导、出院后延续护理等。)